2012
DOI: 10.1080/09596410.2012.676782
|View full text |Cite
|
Sign up to set email alerts
|

The conversion process in stages: new Muslims in the twenty-first century

Abstract: This study deals with stages in the process of conversion to Islam. However, unlike the extensive research on pre-conversion stages, this contribution looks at post-conversion development. The initial stage after conversion brings with it a zealotry in which converts tend to become 'more royal than the king'. The second stage tends to be a period of disappointment with the new peer-group. The third stage is one of acceptance, when converts accept that Muslims are 'ordinary' human beings with shortcomings rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
0
18
0
4
Order By: Relevance
“…Across Europe, a cohort of young Muslim women is popularizing new styles of modest fashion that combines mainstream trends with inventive forms of hijab and Islamic clothing (Lewis 2013;Moors 2009;Moors 2013;Rambo and Bauman 2012;Tarlo 1996;Tarlo and Moors 2013;Van Nieuwkerk 2014). This phenomenon can be seen in the Netherlands (Bartels 2000;Hass and Lutek 2019;Moors 2007;Van Nieuwkerk 2004;Van Nieuwkerk 2014;Vroon 2014), Finland (Almila 2016), Sweden (Roald 2004;Roald 2012), Scotland (Boulanouar 2006), Germany (Ozyurek 2010;Özyürek 2014), France (Bowen 2010;Bowen 2007), and Belgium (Coene and Longman 2008); see also in Rosenberger and Sauer 2013 for more about France, Germany, Austria, Greece, Denmark, UK, Bulgaria and the Netherlands as regards the relationship between veiling and narratives of belonging. One main argument of this book is that the discourse of the veil cuts across and critiques interrelated domains, policies, narratives of national belonging and secularism.…”
Section: Islamic Fashionmentioning
confidence: 92%
“…Across Europe, a cohort of young Muslim women is popularizing new styles of modest fashion that combines mainstream trends with inventive forms of hijab and Islamic clothing (Lewis 2013;Moors 2009;Moors 2013;Rambo and Bauman 2012;Tarlo 1996;Tarlo and Moors 2013;Van Nieuwkerk 2014). This phenomenon can be seen in the Netherlands (Bartels 2000;Hass and Lutek 2019;Moors 2007;Van Nieuwkerk 2004;Van Nieuwkerk 2014;Vroon 2014), Finland (Almila 2016), Sweden (Roald 2004;Roald 2012), Scotland (Boulanouar 2006), Germany (Ozyurek 2010;Özyürek 2014), France (Bowen 2010;Bowen 2007), and Belgium (Coene and Longman 2008); see also in Rosenberger and Sauer 2013 for more about France, Germany, Austria, Greece, Denmark, UK, Bulgaria and the Netherlands as regards the relationship between veiling and narratives of belonging. One main argument of this book is that the discourse of the veil cuts across and critiques interrelated domains, policies, narratives of national belonging and secularism.…”
Section: Islamic Fashionmentioning
confidence: 92%
“…(Quran, chapter 33, verse 59, Shakir translation) Across Europe, a cohort of young Muslim women is at the vanguard of new styles of modest fashion, combining mainstream trends with inventive forms of hijab and Islamic clothing (Bartels 2005;Lewis 2013;Moors 2007Moors , 2013Rambo and Bauman 2012;Tarlo 1996;Tarlo and Moors 2013;Van Nieuwkerk 2003a, 2003b. The same phenomena can also be seen specifically in the Netherlands (Bartels 2000;Moors 2007;Van Nieuwkerk 2003a, 2003b, Finland (Almila 2016); Sweden (Roald 2004(Roald , 2012, Scotland (Boulanouar 2006); Germany (Özyürek 2010, 2014) and France (Bowen 2007(Bowen , 2010. As O'Cass (O'Cass 2004) has argued, these women developed a strong subjective perception of product knowledge and expertise in the product, strongly influenced by their involvement in fashion clothing, as modern fashionable Muslim women.…”
Section: Fashion Anti-fashion and Islamic Fashionmentioning
confidence: 66%
“…The question to be asked here is what gender norms in Dutch society are these women either rejecting completely or modifying? Scholars of religious piety such as Saba Mahmood, and scholars of religious conversion to Islam in the West, such as Anne Sophie Roald and Anna Manson McGinty, found that women embraced non-liberal religious identities not just due to piety but also as rejections of other social models (Avishai 2008;Fader 2009;Mahmood 2001;Marranci Gabriele 2008;Roald 2004Roald , 2012. One possible rejection of a social model could be the concept of 'whiteness' in a Christian based society.…”
Section: Building Identity Through Stylementioning
confidence: 99%
“…Conversion has historically been a popular topic in the study of religion. There has been a particular interest in conversion to Islam in Western contexts (see, among others, King 2017;Köse 1994;McGinty 2006;Özyürek 2014;Roald 2012;Wohlrab-Sahr 2006;van Nieuwkerk 2006van Nieuwkerk , 2008. It has in turn been argued that the concept of 'deconversion' (see, among others, Barbour 1994;Streib et al 2009) should be utilized when people move out of religion, which Barbour (1994, 2) defines as simply 'a loss of faith '.…”
Section: State Of the Artmentioning
confidence: 99%